Ancestry, Socioeconomic Status, and Age-Related Cataract in Asians - Chua, Jacqueline; Koh, Jia Yu; Tan, Ava Grace; Zhao, Wanting; Lamoureux, Ecosse; Mitchell, Paul; Wang, Jie Jin; Wong, Tien Yin; Cheng, Ching-Yu (Ophthalmology (Rochester, Minn.), 2015)
To determine the prevalence of age-related cataract and its ancestral and socioeconomic risk factors in a multi-ethnic Asian population. Population-based, cross-sectional study. A total of 10 033 adults (3353 Chinese, 3280 Malays, and 3400 Indians) aged >40 years in the Singapore Epidemiology of Eye Diseases Study. Study participants were invited for a structured interview and received a standardized comprehensive eye examination. Digital lens photographs were taken from eyes of each participant and graded for nuclear, cortical, and posterior subcapsular (PSC) cataract, following the Wisconsin Cataract Grading System. Prevalence data were compared with the Blue Mountains Eye Study (BMES) in Australia. Information on medical and lifestyle factors was collected using questionnaires and blood samples. To increase the precision of racial definition, genetic ancestry was derived from genome-wide single nucleotide polymorphism markers using principal component analysis. Regression models were used to investigate the association of cataract with socioeconomic factors (education and income) and genetic ancestry. Age-related cataract. A total of 8750 participants (94.0%) had gradable lens photographs. The age-standardized prevalence of cataract surgery in Chinese (16.0%), Malays (10.6%), and Indians (20.2%) was higher than in white subjects (4.1%). We found the age-standardized cataract prevalence in Chinese (30.4%), Malays (37.8%), and Indians (33.1%) was higher than in whites (18.5%). Cataract was 1.5 to 2 times more common in Asians and began 10 years earlier than in white subjects. Malays had significantly higher age-standardized prevalence of nuclear, cortical, and PSC cataract than Chinese (P < 0.001). The severity of nuclear, cortical, and PSC cataract was significantly correlated with genetic ancestry in our South East Asian population. Less education and lower income were associated with cataract for Chinese and Indians but not Malays. The presence of visual impairment associated with cataract was higher in people aged ≥60 years and Malays. We showed that people of different Asian ethnicities had a higher prevalence and earlier age of onset of cataract than Europeans. People of Malay ancestry have a greater severity for all cataract subtypes than people of Chinese ancestry. Education and income were associated with cataract for certain Asian subgroups.